Art for Necessity, Mediumnic Art, Visionaries and Spectators - García Muñoz, Graciela (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2008)
Analyse of creative process in outsider art. We’ll study the reasons that pulse non-artistic people to create spontaneously. To restrain the area we’ll focus on mediumnistic art.